Postinfantile Giant Cell Hepatitis with Features of Acute Severe Autoimmune Hepatitis Probably Triggered by Diclofenac in a Patient with Primary Myelofibrosis - Pinelopi Arvaniti; Kalliopi Zachou; George K. Koukoulis; George N. Dalekos (Case Reports in Hepatology)
Giant cell hepatitis (GCH) is commonly reported in neonatal and infantile liver diseases but rarely in adults where the term postinfantile GCH (PIGCH) is used. PIGCH is associated with many diseases, including drugs toxicity, viruses, and autoimmune liver diseases, with autoimmune hepatitis (AIH) being the most prevalent. We present a case of PIGCH in a 76-year-old female without known history of liver disease who suffered from an acute severe episode of hepatitis. After careful exclusion of other hepatitis causes by imaging, virological, immunological, and microbiological investigations, a diagnosis of acute severe AIH (AS-AIH) was established. The patient was started on corticosteroids but she did not respond and died 3 days later because of advanced acute liver failure. Postmortem liver biopsy showed typical PIGCH lesions. Physicians must keep this catastrophic entity in mind in cases of unexplained acute liver injury as, contrary to our case, prompt rescue therapy with corticosteroids may be life-saving.